HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN PADA PASIEN PRE OPERASI MAYOR DI RUANG BEDAH RUMAH SAKIT TK.II DUSTIRA CIMAHI TAHUN 2024 - Fitri Apriliani, Nur; Setya Roswendi, Achmad; Yuswandi, Yuswandi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background: Surgery is an action that is seen as a frightening experience for patients. Surgery requires patients to adapt, but the adaptability of each patient is different, triggering anxiety. Therefore, support from the family is needed to reduce preoperative anxiety. Objective : This study aims to determine the relationship between family support and anxiety in major preoperative patients in the Dustira Hospital surgical room. Method : The type of research used is correlation with a Cross Sectional approach. The population in this study were patients who would undergo major surgery, while the sample amounted to 67 respondents with purposive sampling. Data were taken directly using a questionnaire and then analyzed with univariate to see the frequency distribution and bivariate to see the relationship between variables. Result : The results of data analysis showed that respondents at Dustira Hospital had high family support (94%) and experienced severe preoperative anxiety (89.6%). There is a strong relationship between family support and anxiety in major preoperative patients in the Dustira Hospital surgical room with a p value = 0.000 ≤ α 0.05. Conclusion: There is a significant relationship between family support and preoperative anxiety in patients undergoing major surgery. The negative correlation indicates an inverse relationship: the higher the level of family support, the lower the level of preoperative anxiety.